Monetary finance - Agur, Itai,Capelle, Damien,Dell'Ariccia, Giovanni,Sandri, Damiano (International Monetary Fund, Publication Services, 2022)
This paper reviews the theoretical arguments in favor and against MF and presents an empirical assessment of the risks that it may pose for inflation
10.5089/9781513592541.087
Keywords: Graue Literatur; Monetary finance; fiscal and monetary coordination; liquidity trap; inflation expectation; UMP announcement; hard-won central bank credibility; support well; UMP program; Global; Inflation; Monetary base; Unconventional monetary policies; Sovereign bonds; Banks and Banking; Monetary Policy; Monetary Policy; Central Banking; and the Supply of Money and Credit: General; Fiscal Policies and Behavior of Economic Agents: General; Price Level; Deflation; General Financial Markets: General (includes Measurement and Data); Financial Crises; Political economy; Monetary economics; Macroeconomics; Investment & securities; Economic & financial crises & disasters; Banking; Money; Financial institutions; Money and Monetary Policy; Investments: Bonds; Financial Risk Management; Monetary policy; Fiscal policy; Prices; Money supply; Bonds; Financial crises